Fratture periprotesiche di femore: confine tra sintesi e revisione - franceschini, M.; De Bartolomeo, O.; Calabrò, F.; Cerbone, V.; Mineo, C.V. (Lo Scalpello - Journal, 2018)
PERIPROSTHETIC FEMORAL FRACTURES: THE BORDER BETWEEN SYNTHESIS AND REVISION The incidence of periprosthetic femoral fractures is increasing due to the growing number of THA all over the world and the older age of the population. This article is a review of the literature and an analysis of our cases; the different surgical treatments were described and evaluated. Attention was paid to the border between synthesis and revision.